2015
DOI: 10.1039/c5ra07421e
|View full text |Cite
|
Sign up to set email alerts
|

Ordered mesoporous crystalline aluminas from self-assembly of ABC triblock terpolymer–butanol–alumina sols

Abstract: A one-pot synthesis approach is described to generate ordered mesoporous crystalline g-alumina-carbon composites and ordered mesoporous crystalline g-alumina materials via the combination of soft and hardtemplating chemistries using block copolymers as soft structure-directing agents. Periodically ordered alumina hybrid mesostructures were generated by self-assembly of a poly(isoprene)-block-poly(styrene)-block-poly(ethylene oxide) terpolymer, n-butanol and aluminum tri-sec-butoxide derived sols in organic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…19,23 Earlier we have reported that the carbon coating deposited on the surface of the oxide nanoparticles can act as a nanoreactor shell. On the one hand, such coating can be penetrable for the reactant molecules from the gas 7,10,24,25 or liquid 26 phases making it possible to initiate various catalytic or solid-state reactions inside the nanoreactor. Moreover, the carbon coating prevents sintering of nanoparticles inside the shell during the temperature increase and stabilizes their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…19,23 Earlier we have reported that the carbon coating deposited on the surface of the oxide nanoparticles can act as a nanoreactor shell. On the one hand, such coating can be penetrable for the reactant molecules from the gas 7,10,24,25 or liquid 26 phases making it possible to initiate various catalytic or solid-state reactions inside the nanoreactor. Moreover, the carbon coating prevents sintering of nanoparticles inside the shell during the temperature increase and stabilizes their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Highly crystalline, ordered mesoporous oxide and carbon materials generated by structuredirecting surfactants and block copolymers (BCPs) are desirable for their tunable periodic morphologies and multifunctional properties, [1][2][3][4][5][6][7] and have been widely deployed in many applications 8 ranging from catalysis, 9,10 energy conversion and storage, [11][12][13][14] adsorption and separation, 15,16 sensing 17,18 and even superconductors. 19 However, conventional routes to form mesoporous inorganic structures with high crystallinity typically require thermal annealing treatments at elevated temperatures (≥600 °C) over long durations (≥10 hours) under controlled environments (e.g., argon, ammonia) for inorganic crystallization, thereby increasing production time and cost.…”
Section: Main Textmentioning
confidence: 99%
“…19 However, conventional routes to form mesoporous inorganic structures with high crystallinity typically require thermal annealing treatments at elevated temperatures (≥600 °C) over long durations (≥10 hours) under controlled environments (e.g., argon, ammonia) for inorganic crystallization, thereby increasing production time and cost. [3][4][5][6][7][15][16][17][18][19] In particular, untamed nucleation and growth of crystallites that occur spontaneously at higher temperatures often result in the collapse of ordered structures. 2,5,7 Alternative nonequilibrium methods have been explored for the rapid formation of single crystal and polycrystalline inorganic nanostructures on shorter time frames.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the practical application is plagued by the poor thermal stability resulted from their amorphous or semi-crystalline pore walls. As a result, design and synthesis of MA with crystalline pore walls has long been a hot topic [5][6][7][8]. Recently, considerable efforts [9][10][11][12] have been devoted to reduce the synthesis cost of crystalline MA by using the inexpensive inorganic aluminum salts to replace aluminum alkoxides.…”
mentioning
confidence: 99%